A Review of Coffee By-Products Including Leaf, Flower, Cherry, Husk, Silver Skin, and Spent Grounds as Novel Foods within the European Union - Tizian Klingel; Jonathan I. Kremer; Vera Gottstein; Tabata Rajcic de Rezende; Steffen Schwarz; Dirk W. Lachenmeier (Foods, 2020)
The coffee plant Coffea spp. offers much more than the well-known drink made from the roasted coffee bean. During its cultivation and production, a wide variety of by-products are accrued, most of which are currently unused, thermally recycled, or used as animal feed. The aim of this review is to provide an overview of novel coffee products in the food sector and their current legal classification in the European Union (EU). For this purpose, we have reviewed the literature on the composition and safety of coffee flowers, leaves, pulp, husk, parchment, green coffee, silver skin, and spent coffee grounds. Some of these products have a history of consumption in Europe (green coffee), while others have already been used as traditional food in non-EU-member countries (coffee leaves, notification currently pending), or an application for authorization as novel food has already been submitted (husks, flour from spent coffee grounds). For the other products, toxicity and/or safety data appear to be lacking, necessitating further studies to fulfill the requirements of novel food applications.